System for Measuring the Socio-Economic Sustainability of the Eurasian Economic Union - Ryazantsev, Sergey V.; Rostovskaya, Tamara K.; Zolotareva, Olga A. (Economy of Regions, 2021)
Whether applying to individual countries or unions, the comparability of statistical indicators and their compliance with contemporary international initiatives is a serious problem. In particular, analysis of the macroeconomic indicators used for assessing the sustainability of the Eurasian Economic Union (EAEU) countries has shown that they do not reflect the actual situation. In this regard, the creation of a unified system of indicators for determining the socio-economic sustainability of EAEU member states — as well as the EAEU as a whole — becomes an urgent task. Therefore, the present study aims to refine the system for measuring the socio-economic sustainability of the Eurasian space and develop recommendations for the selection of key parameters. By comparing socio-economic sustainability indicators published by international organisations (UNECE, OECD, Eurostat, CIS Statistical Committee) in the context of the development strategies of individual EAEU countries and the Union as a whole, the authors distinguish between basic and extended indicator types. Basic indicators comprise: the annual consolidated budget deficit; general government debt; annualised inflation rate; contribution of high-tech and knowledge-intensive industries to gross domestic product (GDP); contribution of innovative goods and services to total industrial exports; growth index of the proportion of reconstruction and modernisation investment to total capital investment; fertility rate; life expectancy at birth; poverty rate. Extended indicators include: GDP; economic growth; main international trade; external and national balance of payments; social. The applicability and relevance of the proposed system for measuring the socio-economic sustainability of the Eurasian space is confirmed by statistical analysis of EAEU member state data (including correlation analysis).